Evaluating pre-anesthesia assessment performance in residency: the reliability of standardized patient methods - Besnier, Emmanuel; Franchina, Sébastien; Lefevre-Scelles, Antoine; Wable, Thierry; Hanouz, Jean-Luc; Allard, Etienne; Dureuil, Bertrand; Compère, Vincent (Frontiers in Medicine, 2024)
Background: Pre-anesthesia assessment clinic (PAC) is known to increase safety and quality in the perioperative period. However, PAC teaching during anesthesiology residency is a challenge. The objective of this study was to assess the reliability of a simulation score grid using a standardized patient on the PAC performance of anesthesiology residents.Methods: A score grid, including the 4 components of the PAC (clinical evaluation, perioperative strategy, information and communication) was validated by a group of 5 senior anesthesiologists. Anesthesiology residents (> one year) and attending anesthesiologists were included. The same simulation sequence with the same standardized patient was conducted in a simulation dedicated consultation room. The simulation sequence was followed by a debriefing session with the 2 professors (anesthesiology and communication) and each anesthesiology resident. The main outcome was the overall grid score out of a maximum score of 300 and the correlation of this score with experience in anesthesiology residency. Secondary outcomes were individual component scores according to level of experience in anesthesiology.Results: Between October 2014 and April 2016, 109 anesthesiology residents and 16 attending anesthesiologists were included in this prospective bicentric study. There was a positive correlation (p<0.01) between level of experience and overall score on the grid score (Pearson's Coefficient = 0.52). The Pearson correlation coefficient between overall assessment and level of experience in anesthesiology was 0.46 (p <0.01). The analysis of the sub-scores for the 4 components of the overall score (evaluation, perioperative strategy, information and communication) also identify differences between groups of experience.Conclusion: Standardized patient Simulation of PAC seems to be a reliable tool to assess PAC performance in anesthesiology residents and senior anesthesiologists. These results suggest standardized patient simulation could be used as a teaching tool for PAC.